2022
DOI: 10.3390/metabo12050466
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study Suggests the Mechanism of Different Types of Tieguanyin (Oolong) Tea in Alleviating Alzheimer’s Disease in APP/PS1 Transgenic Mice

Abstract: Previously, we found that three types of Tieguanyin tea (Tgy-Q, Tgy-N and Tgy-C) extracts could alleviate Alzheimer’s disease (AD) in a mouse model among which Tgy-C was more effective. In this study, APP/PS1 transgenic mice were used to investigate the metabolomic changes in the feces of mice treated with Tieguanyin tea extracts. Results showed that the profile of fecal metabolites was obviously changed in AD mice. Metabolomics analysis found the effects of Tgy-C, especially its decreasing effect on the fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The presence of theanine in tea appears to correlate with improvements in cognitive function [ 19 , 20 ]. Multiple investigations underscore that diverse tea types—ranging from black tea [ 21 ] and white tea [ 22 ] to green tea [ 23 , 24 ] and Oolong tea [ 25 ] — can positively influence mitigating risk factors linked to AD. Nevertheless, the correlation between tea consumption and AD remains an ongoing subject of inquiry, yielding inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of theanine in tea appears to correlate with improvements in cognitive function [ 19 , 20 ]. Multiple investigations underscore that diverse tea types—ranging from black tea [ 21 ] and white tea [ 22 ] to green tea [ 23 , 24 ] and Oolong tea [ 25 ] — can positively influence mitigating risk factors linked to AD. Nevertheless, the correlation between tea consumption and AD remains an ongoing subject of inquiry, yielding inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…Tie Guanyin, a kind of semi-fermented oolong tea, is famous for the unique and elegant floral aroma, and ripe fruity flavor (Yao et al, 2021). Research indicated that Tie Guanyin extracts could alleviate Alzheimer's disease (AD) in a mouse model (Tu et al, 2022). Phenolics obtained from Tie Guanyin exhibited strong antioxidant capacity and inhibition of the growth of 4T1 murine breast cancer cells (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%